2020
DOI: 10.37213/cjal.2020.28958
|View full text |Cite
|
Sign up to set email alerts
|

Metalinguistic Reflection and Computer-Mediated Communication: An Interventionist approach to Language Study Abroad

Abstract: This article reports on part of a mixed-methods study framed by sociocultural theory and aimed at assessing the impact of an intervention to promote metalinguistic awareness in language study abroad sojourners. Participants utilized a social media platform as a space to develop personalized e-portfolios for the purpose of in-depth metalinguistic reflection, paired with entirely computer-mediated researcher-participant mentoring. As such, this study addresses the importance of intervention in second language le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 27 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…SM-based e-Portfolios benefited students in developing their skills. Past studies reported students’ skill development in areas as follows: language (Gordon, 2017 ; McGregor, 2020 ) and language learning skills (Gordon, 2017 ); writing abilities (Aydin, 2014 ; Barrot, 2021 ; Gabaudan, 2016 ; Kabilan & Khan, 2010 ; Rubrico, 2012 ; van Wyk, 2017 ; Wicks & Lumpe, 2015 ); reading skills (Aydin, 2014 ; Barrot, 2016 ; Kabilan & Khan, 2010 ); speaking skills (Huang & Hung, 2010 ; McGregor, 2020 ); critical thinking skill (Blaschke, 2014 ; Cleveland, 2018 ; Kabilan, 2016 ; Kabilan & Khan, 2010 ; van Wyk, 2017 ); technological skills (Gabaudan, 2016 ; Kabilan & Khan, 2010 ; Tur & Marín, 2015 ; Tur & Urbina, 2014 ); research skills (Aydin, 2014 ); designing skills and knowledge of different cultures (Gordon, 2017 ); teaching skills and organization skills (Kabilan, 2016 ); scientific literacy (Wijayanti & Basyar, 2016 ); and vocabulary (McGregor, 2020 ). …”
Section: Findings and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SM-based e-Portfolios benefited students in developing their skills. Past studies reported students’ skill development in areas as follows: language (Gordon, 2017 ; McGregor, 2020 ) and language learning skills (Gordon, 2017 ); writing abilities (Aydin, 2014 ; Barrot, 2021 ; Gabaudan, 2016 ; Kabilan & Khan, 2010 ; Rubrico, 2012 ; van Wyk, 2017 ; Wicks & Lumpe, 2015 ); reading skills (Aydin, 2014 ; Barrot, 2016 ; Kabilan & Khan, 2010 ); speaking skills (Huang & Hung, 2010 ; McGregor, 2020 ); critical thinking skill (Blaschke, 2014 ; Cleveland, 2018 ; Kabilan, 2016 ; Kabilan & Khan, 2010 ; van Wyk, 2017 ); technological skills (Gabaudan, 2016 ; Kabilan & Khan, 2010 ; Tur & Marín, 2015 ; Tur & Urbina, 2014 ); research skills (Aydin, 2014 ); designing skills and knowledge of different cultures (Gordon, 2017 ); teaching skills and organization skills (Kabilan, 2016 ); scientific literacy (Wijayanti & Basyar, 2016 ); and vocabulary (McGregor, 2020 ). …”
Section: Findings and Discussionmentioning
confidence: 99%
“…Students’ language and language learning skills have substantially improved because they have to think about linguistics almost all the time while maintaining their e-Portfolio (Gordon, 2017 ). McGregor ( 2020 ) highlights that the use of SM-based e-Portfolio during language study abroad promoted metalinguistic awareness. It can significantly impact language gain because students had the opportunity to reflect on their language learning and pose questions to an expert mentor (McGregor, 2020 ).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations